Mortality rate of mental disorder trends in China from 2002 to 2020 - Li, Boxuan; Zhang, Guoshuang; Ma, Jing; Kang, Mingxiu (Frontiers in Psychiatry, 2022)
Background The number of people with mental disorders is increasing in China, but there are few studies on the temporal trends and population distribution of mental disorder mortality. Methods The mortality of mental disorders were derived from the China Health Statistics Yearbook published by the National Health and Family Planning Commission. Temporal trends in mortality were examined with a joinpoint regression using annual percent change (APC) and average annual percent change (AAPC). A Poisson regression model was utilized to test the population-level risk factors associated with the death of people with mental disorders. Results The mortality of mental disorders in rural Chinese residents showed a decreasing trend from 2002 to 2020 [AAPC –2.06%, 95% confidence interval (CI) –3.16 to –0.91%]. The mortality of mental disorders in urban Chinese residents declined between 2005 and 2011 (APC –13.01%, 95% CI –21.08 to –4.13%). The mortality rate of mental disorders has decreased for urban males with an APC of –2.71% (95% CI –4.52 to –0.71) from 2002 to 2020. Urban women showed an increase in mental disorder mortality from 2002 to 2005 and from 2012 to 2020 with APCs of 19.65% (95% CI 0.64–42.32%) and 6.16% (95% CI 2.22–10.33%), respectively. Age was a significant risk factor for mental disorder mortality (odds ratio 1.28, 95% CI 1.23–1.32). Conclusion The dissemination of medical and health information, investment in medical and health resources, and the modification and optimization of regulations have led to a decrease in mental disorder mortality in China. It is vital to devote greater attention to elderly individuals suffering from mental disorders.